The Role of Emotional Factors in Developing Consumer and Brand Relations in the Medical Tourism Industry. Case Study: Hospitals of Shiraz City - AZIMI, Hossein (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
Medical tourism is a process in which a person travels outside their living place to receive medical care and resides there for some time. Therefore, attention to this particular type of tourism can be effective in economic growth. This study examines how emotional relationships between consumers and brands affect medical tourism. In terms of purpose, this research is application-oriented and is descriptive-analytic in terms of method of work. Questionnaires were used for data collection. The statistical population of this study were all non-indigenous patients in Shiraz hospitals and the statistical sample was Cochran formula according to 300 non-indigenous patients in different wards of these hospitals which were selected by simple random sampling. The conceptual model of the research was designed using structural equation modelling and PLS software. The results showed that the effects of emotional commitment on brand loyalty and brand loyalty on brand loyalty in medical tourism were rejected and the rest of the hypotheses were confirmed which among them the effect of emotional commitment on brand loyalty with 65.6%, the effect of emotional commitment on the brand relationship with 62.9%, the effect of the brand relationship on brand loyalty with 60.1% and the effect of brand confidence on emotional commitment with 59.2% had the highest impacts on the model.